O princípio da solidariedade social nas relações entre particulares : implicações da boa-fé objetiva na interpretação dos contratos empresariais - Tavares, Cláudio Kaminski (2017)
This essay has as its goal to analyze the interpretation of business contracts in accordance with the principle of good faith. It begins with an introduction of the theme, in a chapter is made a historical analysis of the good faith, followed by an account of its reception in Brazilian law, of its acting as a hermeneutic and integrative canon, and, at the end, of the examination of the relationship between good faith and the constitutional principle of social solidarity. In the second chapter is made a study of the business contracts, identifying their concept and their peculiar discipline. After, it aims to distinguish the business contracts from the civil and consumer contracts and to identify some characteristics inherent to the business contracts. It also analyzed the treatment of the doctrine about economic dependence on business contracts. Finally, the work is restricted to analyzing the interpretation of the contracts in accordance with and to identify some guidelines that can aid the process of interpretation.